2020
DOI: 10.1098/rsos.191663
|View full text |Cite
|
Sign up to set email alerts
|

Research on stress release for the gob-side roadway using the roof-cutting technology with a chainsaw arm

Abstract: Research on stress release for the gob-side roadway using the roof-cutting technology with a chainsaw arm. R. Soc. open sci. 7: 191663. http://dx.measured results indicated that the peak advancing stresses decreased by 22.8% on average, and therefore, roof cutting and stress releasing effects were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…15,16 The reason why this technology is replaced by NPRP is completely due to the low recovery rate, which is not conducive to the sustainable development of the mine and coal industry. 17,18 2.1.2 | GSER layout mode NPRP includes GSER and EDGS. Among which, only GSER could be strictly called NPRP strictly, because there is no coal pillar between the adjacent working face.…”
Section: Dre Layout Modementioning
confidence: 99%
“…15,16 The reason why this technology is replaced by NPRP is completely due to the low recovery rate, which is not conducive to the sustainable development of the mine and coal industry. 17,18 2.1.2 | GSER layout mode NPRP includes GSER and EDGS. Among which, only GSER could be strictly called NPRP strictly, because there is no coal pillar between the adjacent working face.…”
Section: Dre Layout Modementioning
confidence: 99%
“…For the second numerical model, a constraint was imposed on the bottom for restricting vertical displacement, 30 and linear loads were applied on two sides. The fault was described by a “Structure Interface.” 31 The models were meshed into many triangular elements. For the first model, 29,851 elements and 16,937 nodes were generated.…”
Section: Numerical Model For Precontrolling Rock Burst Via Ground Fra...mentioning
confidence: 99%
“…Zheng [11] developed a mechanical model of gob-side roadway overburdens to analyze the large deformation and stress field distribution. In order to mitigate the problem of the coal pillar extrusion and serious deformation that will occur in the gob-side roadway, Tai [12] developed the roof-cutting technology with a chainsaw arm and its equipment. Zhang [13] investigated the effects of dynamic loading to gob-side entries and optimized the support parameters; the field test results showed that the potential for loosening, deformation, and failure of the surrounding rock were effectively controlled.…”
Section: Introductionmentioning
confidence: 99%